Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1111/jnc.15360
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway metabolites in cerebrospinal fluid and blood as potential biomarkers in Huntington's disease

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 64 publications
0
16
0
Order By: Relevance
“…The activation of neuroinflammatory response and microglia could further increase the activity of IDO and KP downstream ( 4 ). A recent study conducted on 40 premanifest HD patients, 40 manifest HD patients, and 20 HCs, denied the alteration of KP during HD pathogenesis ( 108 ). In contrast, we found that blood levels of TRP and KYN were significantly lower in HD patients than controls (SMD=-0.90, 95% CI=-1.71 to -0.10, p=0.028, I2 = 91.0%, k=5, n=369) ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…The activation of neuroinflammatory response and microglia could further increase the activity of IDO and KP downstream ( 4 ). A recent study conducted on 40 premanifest HD patients, 40 manifest HD patients, and 20 HCs, denied the alteration of KP during HD pathogenesis ( 108 ). In contrast, we found that blood levels of TRP and KYN were significantly lower in HD patients than controls (SMD=-0.90, 95% CI=-1.71 to -0.10, p=0.028, I2 = 91.0%, k=5, n=369) ( Table 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, there are too few studies on these two genes, and we cannot yet explain the relationship of these two genes with the phenotype. Furthermore, among the genes with nominal significance levels, many were associated with grip strength and depression: (1) FNBP1 can affect neuronal dendrites [ 64 ] and actin [ 65 ], which may affect grip strength and depression; (2) MOG is associated with multiple sclerosis [ 66 , 67 ], the main symptoms of which include depression and decreased muscle strength; (3) the SACS gene can affect motor and sensory neuropathy [ 68 ], and is associated with complex neurological disorders [ 69 ]; (4) the KMO gene is associated with depression [ 70 , 71 ] and Huntington’s disease [ 72 ], the symptoms of which include muscle atrophy; (5) the TECPR2 gene is tightly linked to the nervous system [ 73 76 ] and may influence depression and grip strength by affecting nerves; and (6) MGTA5 can affect the severity of multiple sclerosis [ 77 , 78 ]. MGTA5 may also be associated with attempted suicide [ 79 ], and therefore may be associated with depression.…”
Section: Discussionmentioning
confidence: 99%
“…The presence of KYNA in human cerebrospinal fluid has been repeatedly reported ( Table S2 ). The content of KYNA in cerebrospinal fluid obtained from adult healthy humans ranges from 0.0009 to 0.005 μM [ 16 , 20 , 21 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. The content of KYNA in cerebrospinal fluid obtained from children is within the same limits [ 38 ].…”
Section: Distribution Of Kynurenic Acidmentioning
confidence: 99%